Optimization and characterization of ultrasonically treated jackfruit seed starch - Mohamad Yazid, Nurulain Syuhada (2022)
Jackfruit seeds contain a high amount of starch but its native is unable to attain required specifications for food industrial applications and researchers are looking for an addition in current available starch products in market. Thus, the aim of this study is to modify jackfruit seed starch (JSS) from a variety of J33 on its physicochemical properties by applying ultrasound treatment. Starch from jackfruit seed was isolated using distilled water and grinded into powder for analysis. The significant effect of factors (starch concentration and ultrasound time) towards responses (paste viscosity, moisture content, and paste clarity) was analysed prior to optimization. Physicochemical properties of the native and ultrasonically treated JSS were then analysed. The results suggested that the paste viscosity of 22.93±13.66cP, moisture content of 10.77±0.07%, and paste clarity of 0.15±0.02% can be achieved at 45% starch concentration and 5 min sonication time. Ultrasound treatment caused the paste viscosity of JSS to be more viscous at 58.14% compared to the untreated JSS. However, in terms of moisture content and paste clarity, the ultrasonically treated JSS exhibited a reduction in value at 17.15% and 37.5% compared to the untreated JSS. In conclusion, JSS can be utilized as an addition to the currently available commercial native and chemically modified starch.